How Social Networks will Change Research - Narayanan, Kulathuramaiyer (IPSI BgD, 2016)
Social Networks have become an integral aspect of our lives in recent years. Developments such as the small-world phenomenon, social curation, and eCommunities are evolving as noteworthy game-changers in an emergent web ecosystem. This paper describes how the way of conducting academic research will change when the resulting omnipresent communication and sharing technology is taken into account. Researchers will have no choice but to embrace SN technologies to fully exploit the true potential of the emerging ecosystem.